The economic advantage: assessing the value of climate change actions in agriculture - Vermeulen, Sonja J.; Richards, Meryl B.; Pinto, Alex de; Ferrarese, Dino; Läderach, Peter R.D.; Lan, Le; Luckert, Marty; Mazzoli, Enrico; Plant, Laura; Rinaldi, Roberto; Stephenson, Jim; Watkiss, Paul (2016)
This brief summarizes an International Fund for Agricultural Development (IFAD) report: The Economic Advantage: assessing the value of climate-change actions in agriculture. The report informs readers who seek to build economic evidence in support of the inclusion of actions on agriculture in climate change plans and programs, particularly at the national level, for example the nationally determined contributions (NDCs) to the December 2015 Paris Climate Agreement, National Adaptation Plans (NAPs) and related policy instruments.